2022
DOI: 10.3201/eid2811.220577
|View full text |Cite
|
Sign up to set email alerts
|

Differences in SARS-CoV-2 Clinical Manifestations and Disease Severity in Children and Adolescents by Infecting Variant

Abstract: rapidly spread worldwide, causing a global pandemic with major social and economic disruption. Although the effects of COVID-19 have been greater in adults, children also are infected with SARS-CoV-2, and COVID-19 can lead to severe outcomes in pediatric patients (1-3). Nevertheless, the spectrum of clinical manifestations in children is broad and ranges from asymptomatic to mild upper respiratory infection to pneumonia or the more severe multisystem inflammatory syndrome in children (MIS-C), which typically o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
26
3
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 51 publications
6
26
3
2
Order By: Relevance
“…Our findings support previous observations in other countries. 7,11,12 Contrary to our study, other retrospective studies have found that the Omicron period is less severe than different periods, including the Delta predominant period. This heterogeneity among research results may affect study design.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our findings support previous observations in other countries. 7,11,12 Contrary to our study, other retrospective studies have found that the Omicron period is less severe than different periods, including the Delta predominant period. This heterogeneity among research results may affect study design.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, it was observed that the age distribution of hospitalized patients changed in the Omicron period compared to other periods; the proportion of children <1‐year‐old increased, and the proportion of children aged ≥12 years decreased. Our results were in line with research from the United States, the United Kingdom, and Germany that found a higher percentage of newborns and young children hospitalized with COVID‐19 during the Omicron wave 7–10 . A similar observation was also emphasized in studies in different regions 11–14 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations